Entanglement and teleportation via partial entangled-state quantum network - Abdel-Aty, A.-H. (American Scientific Publishers, 2015)
A partially entangled network is generated between four nodes by using two pairs of Werner state. The non-connect nodes are connected via the Dzyaloshiniskii-Moriya (DM) interaction. The effect of DM' strength and its directions on the degree of entanglement is discussed. It is shown the upper bounds of entanglement, which is generated between two nodes via indirect interaction is much better than the others. The possibility of using this network to teleport unknown quantum state between any two terminals is investigated. We show that, by controlling on the strength of DM and its direction, one can teleport states with high fidelity. Â© 2015 American Scientific Publishers All rights reserved.